Towards consumers' Coffee Shop patronization using loyalty programs - Abenoja, Rowella Maan M., Basilog, Jolly Ven G., Campo, Shaina Mae Y., Javierto, Rosenda Mae R., Ladaran, Carl Terry A., Rubia, Liza R., Versola, Carla May P. 4 0 16; 5
Abstract Loyalty programs have become increasingly prevalent in the coffee industry, aiming to enhance customer loyalty and stimulate repeat purchases. By analyzing the influencing factors of the loyalty programs of the selected coffee shops in District 4, City of Manila towards consumers' coffee shop patronization, this research aimed to provide intuitions into their effectiveness and identify key attributes that drive customer engagement and satisfaction. A survey questionnaire was administered to 150 respondents, and the findings disclose several key insights. It was tested in the study that the Four Cs of Customer Loyalty as basis to determine the the level of patronization of respondents in a coffee shop are highly patronized by the respondents. Furthermore, the influence of coffee shop patronization with loyalty programs is highly influential.
Research Paper: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2